The Use of English Language Learning Strategy Viewed from Intrinsic Motivation and Learning Style - rachmawati, dwita laksmita; Putri, Widyarini Susilo (EnJourMe (English Journal of Merdeka) : Culture, Language and Teaching of English, 2017)
This study was held to find English learning strategy used by 120 students of Faculty of Economics Universitas Merdeka Pasuruan and to discover their different level of intrinsic motivation and learning style. Oxfords theory of language learning strategy (1990), Amabiles theory of intrinsic motivation (1994) and Reids theory of learning style (1987) were employed in this study. The data obtained from Language Learning Strategy Scale, Intrinsic Motivation Scale and Learning Style Scale, analyzed with two way of ANOVA statistical technique. The results explained that there was a significant difference of language learning strategy applied by the students with high, moderate and low level of intrinsic motivation (F = 40.756, p < 0.05). There was no significant difference of learning strategy used by the students with auditory, visual, individual or group learning style. Social and meta-cognitive strategies were the most frequent strategy applied by all the students. Visual learning style and group styles were dominantly applied by Economics students 2016/2017 academic year.